2001
DOI: 10.1007/s00464-001-0037-z
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic responses to intrapleural insufflation with hemipulmonary collapse

Abstract: The hemodynamic effect resulting from one-lung collapse plus low-flow CO2 insufflation at 8-10 mmHg for 30-40 min is mild in both hemithoraces, although the impact is greater on the right.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 10 publications
(11 reference statements)
0
18
0
Order By: Relevance
“…Few studies have investigated the hemodynamic consequence of CO 2 insufflation, and all of these reports were done in adult thoracoscopy. 14,15 To the best of our knowledge, there has been no report concerning the cardiovascular effects of increased intrapleural pressure in the pediatric population during VATS.…”
Section: Discussionmentioning
confidence: 95%
“…Few studies have investigated the hemodynamic consequence of CO 2 insufflation, and all of these reports were done in adult thoracoscopy. 14,15 To the best of our knowledge, there has been no report concerning the cardiovascular effects of increased intrapleural pressure in the pediatric population during VATS.…”
Section: Discussionmentioning
confidence: 95%
“…Toshiya Ohtsuka and associates had previously reported that the central venous and pulmonary capillary wedge pressures were significantly elevated and the cardiac index was decreased slightly during CO 2 insufflation with hemipulmonary collapse [7]. The present alternative method of sternum lifting was used successfully in 12 consecutive patients.…”
Section: Commentsmentioning
confidence: 79%
“…Insufflation also enlarges the intrapleural space by pushing the mediastinum away from the operative field [1]. The technique is often used in thoracoscopic harvesting of the internal mammary artery.…”
Section: Discussionmentioning
confidence: 99%